Exploring avenues for agricultural intensification in the United States - Massigoge, Ignacio (Kansas State University, 2024)
Crop intensification is a key aspect for achieving global food security and exploring options for optimizing the use of land and environmental resources. Alternatives to increase production without increasing land area (herein termed as crop intensification) are limited to i) increasing the yield of a single crop per year per unit of land area, and/ or ii) increasing the number of crops harvested per year. This dissertation is organized into six chapters (Chapter 1, General Introduction, and Chapter 6, Final Remarks) that present different case studies of crop intensification in major field crop production regions of the United States (US). Chapter 1 provides a general context for global food demand and the resulting need to intensify cropping systems. Chapter 2 explores different crop management strategies represented as combinations of planting dates by hybrid maturity to optimize rainfed maize grain yield in the central Great Plains region of the US, while Chapter 3 investigates alternative crop rotations, including summer field crops, relative to continuous winter wheat cropping systems within the same region. Chapter 4 offers a new perspective on crop rotations via exploring the feasibility of cultivating maize-soybean double cropping system in the US Southern region, integrating field data with the APSIM crop growth model. The analyses developed in Chapter 5 revealed patterns of soybean yield deceleration and stagnation relative to maize for Kansas and the most relevant crop production region, the US Corn Belt. Lastly, Chapter 6 provides a summary of key findings and directions to guide future research linked to crop intensification in the United States and globally.
Keywords: Crop diversification; Rotation productivity; Management practices; Crop modeling